2019
DOI: 10.1007/s11837-019-03334-w
|View full text |Cite
|
Sign up to set email alerts
|

Repeatedly Applied Peptide Film Kills Bacteria on Dental Implants

Abstract: The rising use of titanium dental implants has increased the prevalence of peri-implant disease that shortens their useful life. A growing view of peri-implant disease suggests that plaque accumulation and microbiome dysbiogenesis trigger a host immune inflammatory response that destroys soft and hard tissues supporting the implant. The incidence of peri-implant disease is difficult to estimate, but with over 3 million implants placed in the USA alone, and the market growing by 500,000 implants/year, such exte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(44 citation statements)
references
References 49 publications
(54 reference statements)
1
42
0
Order By: Relevance
“…Warnke et al reported a recombinant human beta defensin-2 coating for biocompatibility assessment with the human mesenchymal stem cells (hMSCs) and human osteoblasts, and found no toxicity [278]. Bifunctional peptide binding (BPB) on the titanium discs were engineered in this study to combat the S. mutans bacteria, and the results were promising for the coating on dental implants due to antibacterial and antibiofouling activity over the four fouling/cleaning cycles [279]. Human saliva contains many antimicrobial proteins and peptides (defensins, cathelicidins, histatins, statherins, and proline-rich peptides), which are useful for oral health.…”
Section: Antimicrobial Peptides (Amps) Coatingsmentioning
confidence: 90%
“…Warnke et al reported a recombinant human beta defensin-2 coating for biocompatibility assessment with the human mesenchymal stem cells (hMSCs) and human osteoblasts, and found no toxicity [278]. Bifunctional peptide binding (BPB) on the titanium discs were engineered in this study to combat the S. mutans bacteria, and the results were promising for the coating on dental implants due to antibacterial and antibiofouling activity over the four fouling/cleaning cycles [279]. Human saliva contains many antimicrobial proteins and peptides (defensins, cathelicidins, histatins, statherins, and proline-rich peptides), which are useful for oral health.…”
Section: Antimicrobial Peptides (Amps) Coatingsmentioning
confidence: 90%
“…as well as changing the design and composition of implants ( Cooper et al, 2016 ; Wang Y. et al, 2019 ) are generally proposed as available strategies. Additionally, biofilm consisted of various subgingival bacteria may form upon the material at once after implantation, which stimulates excessive inflammatory response provided that microbiome dysbiosis occurs, leading peri-implant mucositis or even peri-implantitis that threatens the stability and survival of dental implants ( Wisdom et al, 2019 ).…”
Section: Osteogenesis Angiogenesis and Osteoimmunology And Their Effmentioning
confidence: 99%
“…With the emergence of bacterial resistance, antimicrobial peptides, which are naturally integrated in the oral fluids, are getting high attention as a promising solution to prevent bacterial infections at the a/d interface . Building upon the strength of our research team in antimicrobial peptide design and application at biomaterial interfaces, we modified an antimicrobial peptide sequence to integrate into a dental adhesive system. The antimicrobial peptide coupled adhesive formulations demonstrated significant antimicrobial activity with the resin, when applied to the discs .…”
Section: Peptide Engineering and Dentin Adhesivesmentioning
confidence: 99%